Case Report: Concurrence of Dermatomyositis and Autoimmune Blistering Diseases: Two Case Reports and a Literature Review - Wu, Haixi; Diao, Licheng; Xue, Ke; Zhao, Qian; Zhao, Xiaoqing; Xia, Qunli; Zheng, Jie; Pan, Meng; Cao, Hua (Frontiers in Immunology, 2022)
Dermatomyositis (DM) is an idiopathic inflammatory myopathy primarily involving skin and muscles, and clinically amyopathic DM (CADM) is a subset of DM presenting characteristic cutaneous manifestations but no clinical evidence of myositis. Though rare, vesiculobullous eruptions could develop with DM patients. This situation is termed “bullous DM” and commonly regarded as a signal of internal malignancy. However, some mimic cases were diagnosed as autoimmune blistering disease eventually. Herein, we reported two cases of CADM with autoimmune blisters formed. Case 1 presented vesicles when the diagnosis of CADM was made, and we described the situation with “bullous CADM”. Unexpectedly, the patient developed blisters again years later but the diagnosis turned out to be “pemphigus foliaceous” this time. As far as we know, it has not been reported that two different patterns of blisters formed with the same DM patients. Case 2, with a history of nasopharyngeal carcinoma and CADM, developed bullous pemphigoid several days after a use of warmer sticker on abdominal area. The association between disease occurrence and local skin damage might provide more evidence to support the “epitope spreading” hypothesis. Moreover, we reviewed related literatures and discussed the differences between the two mimics in clinic, pathogenesis, therapy, and the risk of complications.